ASTUDYONEMPLOYEE’SSTRESS, WORK-LIFE BALANCE AND COPING MECHANISM IN BENGALURU. (International Journal of Food and Nutritional Sciences, 2022)
Employees in the corporate sector in Bengaluru, India, are the focus of this research, which examines their exposure to something and management of occupational stress as well as the connection between the two. Primary information was gathered from 175 Bengaluru, India, business professionals. Diverse statistical techniques as well as applications are utilized to examine the data. This same analysis revealed so both occupational stress and work-life balance were moderate. The study's findings suggest that no matter where it manifests itself—at work or at home—stress is an unavoidable fact of life. Various stress-relieving exercises, such as physical activity, spirituality, as well as, most pertinently, trying to detach themself from of the stressful environment, have been recommended for effective managing stress, considering the adverse connection among Work - related Stress and Job-Life Balance.